Typical Mistakes during Investigation of Crimes Committed by Youth Informal Groups Members - Larkin, Mikhail; Biryukova, Alina; Makarenko, Tamara; Ivanova, Natalia; Fedchyniak, Artur (Cuestiones Políticas, 2020)
The main objective of the study is to identify errors made by investigators and other persons authorized to investigate crimes during the process of investigating crimes committed by representatives of informal juvenile criminal groups. Problems related to the failure to present a version of the participation of members of an informal group of young people in crime have been identified. Some aspects of misuse of special knowledge were also considered. During the work, the scientific literature dedicated to the fight against crime, investigation of collective crimes, informal youth groups (associations, movements, etc.) was also analyzed. In addition, a set of different scientific methods was used, such as analysis method, synthesis method, extrapolation method, generalization method. Among the most relevant conclusions it stands out that the problem of juvenile delinquency is becoming general every year, a typical phenomenon not only in Ukraine, but also in other countries in the world; consequently, there is an urgent need to develop new interdisciplinary methods to combat this phenomenon and to understand its multidimensional causes and consequences.